Angiogenic inhibition in high-grade gliomas: past, present and future. (June 2012) - Jo, Jasmin; Schiff, David; Purow, Benjamin
High-grade gliomas, especially glioblastoma (GBM), are among the most aggressive and vascularized tumors. Angiogenesis plays a significant role in tumor growth and survival, and thus offers a target for anticancer treatment. Bevacizumab, a humanized monoclonal antibody against VEGF, was approved by the US FDA as a single agent for the treatment of recurrent glioblastoma. Significant radiographic response and progression-free survival were seen with bevacizumab treatment. However, benefits to overall survival remain undetermined. Other antiangiogenic strategies targeting VEGF, VEGF receptor (VEGFR) and other angiogenic factors have also been examined. Tumor progression after antiangiogenic treatment is inevitable, and effective salvage therapy is yet to be identified. Mechanisms of resistance to antiangiogenic therapy include activation of alternative proangiogenic pathways and increased tumor invasion. Strategies targeting these escape mechanisms are currently being investigated. The use of antiangiogenic drugs is generally well tolerated, although rare and potentially life-threatening adverse effects have been identified. With the striking antipermeability effect of anti-VEGF inhibitors, assessment of true tumor response has become a challenge. The Response Assessment in Neuro-Oncology Working Group has developed new criteria for clinical trials in patients with high-grade glioma. Identification of neuroimaging advances and biologic markers will greatly enhance treatment strategies for these patients.